`2x^3 +6x^2 =x^2 +3x`
`<=> 2x^3 +6x^2 -x^2 -3x=0`
`<=> 2x^3 +5x^2 -3x=0`
`<=> x(2x^2 +5x-3)=0`
`<=> x(2x^2 +6x-x-3)=0`
`<=> x[2x(x+3)-(x+3)]=0`
`<=> x(2x-1)(x+3)=0`
\(< =>\left[{}\begin{matrix}x=0\\2x-1=0\\x+3=0\end{matrix}\right.\\ < =>\left[{}\begin{matrix}x=0\\x=\dfrac{1}{2}\\x=-3\end{matrix}\right.\)
b)
`(2+x)^2 -(2x-5)^2=0`
`<=> (2+x-2x+5)(2+x+2x-5)=0`
`<=> (-x+7)(3x-3)=0`
\(< =>\left[{}\begin{matrix}-x+7=0\\3x-3=0\end{matrix}\right.\\ < =>\left[{}\begin{matrix}x=7\\x=1\end{matrix}\right.\)
`a) 2x^3 + 6x^2 = x^2 + 3x`
`=> 2x^3 + 6x^2 - x^2 - 3x = 0`
`=> 2x^3 + 5x^2 - 3x = 0`
`=> x(2x^2 + 5x - 3) = 0`
`=> x (2x^2 + 6x - x - 3) = 0`
`=> x [(2x^2 + 6x) - (x+3)] = 0`
`=> x [2x(x+3) - (x+3)] = 0`
`=> x (2x - 1)(x+3) = 0`
`=> x = 0` hoặc `2x - 1 = 0` hoặc `x + 3 = 0`
`=> x = 0` hoặc `x = 1/2` hoặc `x = -3`
`b) (2+x)^2 - (2x-5)^2 = 0`
`=> (2+x+2x-5)(2+x-2x+5) = 0`
`=> (3x - 3)(7-x) = 0`
`=> 3x - 3 = 0` hoặc `7 - x = 0`
`=> x = 1` hoặc `x = 7`